A dynamic prediction score for obstetric anal sphincter injury among nulliparous women delivering vaginally. Issue 2 (2nd June 2021) - Meyer, Raanan; Schwartz, Anat; Horesh, Nir; Alcalay, Menachem; Ram, Edward; Levin, Gabriel
Abstract: Objective: To develop a risk score for obstetric anal sphincter injury (OASI) occurrence among nulliparous women delivering vaginally, based on data available at admission for delivery and as labor progresses. Methods: A retrospective study of all nulliparous women who delivered vaginally between March 2011 and January 2021. Characteristics were compared between OASI and no‐OASI groups. Multivariable analyses were performed to identify independent risk factors for OASI occurrence. Results: OASI occurred in 453 (1.7%) of 26 081 women who met the inclusion criteria. The following variables were independently associated with OASI: maternal height (adjusted odds ratio [aOR] 0.97, 95% confidence interval (CI) 0.95–0.99), hypertensive disorders (aOR 1.74, 95% CI 1.03–2.95), sonographic fetal weight estimation (aOR 1.00, 95% CI 1.00–1.00), second‐stage duration (aOR 1.00, 95% CI 1.00–1.00), occiput posterior position (aOR 2.87, 95% CI 1.79–4.62), and episiotomy performance (aOR 0.63, 95% CI 0.47–0.84). In a risk score based on variables available at admission for delivery, the presence of two factors was associated with 4.3% OASI risk. Upon incorporating intrapartum variables, the presence of two risk factors was associated with 2.9% OASI rate. Conclusion: A dynamic risk score for OASI occurrence based on data available at admission for delivery and as delivery progresses can assist in counseling regarding OASI risk. A dynamic risk score for obstetric anal sphincter injury occurrence based on data available at admission for delivery and intrapartum was developed. Abstract : A dynamic risk score for obstetric anal sphincter injury occurrence based on data available at admission for delivery and intrapartum was developed.